Evaluation Of Risk Based Internal Audit In Microbusiness Banking, Consulting And Evaluation Research: Pt Bank Bri (Persero) Tbk. Solo Slamet Riyadi - , RAHMANIAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The paradigm of internal audit has shifted from the traditional/compliance approach to the risk based approach, following the globalization era that required management to be able to manage the risk that have been increased periodically. The risk based approach requires the internal audit to be able to identify and assess risk to provide value added to the management. Itâs also believed that the risk based approach make the internal audit work become fewer because they only focus on the riskier area. The objectives of this paper is to provide evidence that by implementing risk based internal audit, the internal auditor can provide value added to the organization in term of risk identification. With regard of the specific focus, risk based internal audit can also minimizing the work of internal auditor, hence this paper would also aim to provide evidence that the duration and amount of paperwork would be lower if the risk based internal audit is implemented. This research would be conducted by participant observation in one of PT. Bank BRI Tbk. office, while the required data would be collected by observation and interview to the personnel related to their internal audit process. The data would be processed mostly by analysis and comparison study.